2013
DOI: 10.2169/internalmedicine.52.9379
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-induced Paraparesis: Spinal Epidural Lipomatosis Complicated by a Wedge Deformity of the Middle Thoracic Vertebrae

Abstract: Steroid therapy is commonly prescribed, although a variety of complications have been reported. Among such complications, spinal epidural lipomatosis is rare and difficult to diagnose before paraparesis occurs. The purpose of this report is to present a rare but catastrophic complication of steroid therapy. A 64-year-old woman undergoing long-term steroid therapy suffered from an osteoporotic vertebral compression fracture and was unable to walk due to paraparesis. Magnetic resonance imaging (MRI) demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Steroid-induced SEL (both exogenous and endogenous) has been reported to cause spinal cord compression in SEL patients, including acute-onset paraplegia. 38 -41 Most cases occurred following an acute thoracic compression fracture due to osteoporosis in the setting of long-term exposure to steroids, and required urgent surgical decompression. 38 -41 In light of these findings, it may be prudent to monitor bone density in patients being treated for SEL, as compression fractures in the setting of excess epidural fat may have significantly increased morbidity.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Steroid-induced SEL (both exogenous and endogenous) has been reported to cause spinal cord compression in SEL patients, including acute-onset paraplegia. 38 -41 Most cases occurred following an acute thoracic compression fracture due to osteoporosis in the setting of long-term exposure to steroids, and required urgent surgical decompression. 38 -41 In light of these findings, it may be prudent to monitor bone density in patients being treated for SEL, as compression fractures in the setting of excess epidural fat may have significantly increased morbidity.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Tobler et al noted that while the relationship of lipomatosis to exogenous steroids had been demonstrated, the necessary dose or duration of exposure was not clear [28]. Using periodic CT scans, one study demonstrated that the thickness of epidural fat mirrored the dose of steroids [22]. Reviews of fewer patients have presented inconsistent data.…”
Section: Discussionmentioning
confidence: 99%
“…In 22 patients, both the cumulative dose of prednisone and the extent of ultimate recovery could be assessed [7,8,10,11,13,14,17,18,20,[22][23][24][26][27][28][29][30]. Five of these patients were managed conservatively with reduction of their steroid dose, 13 were managed with surgery alone and four were managed with both surgery and steroid reduction.…”
Section: Cumulative Steroid Dosementioning
confidence: 99%
See 1 more Smart Citation
“…7,8 On rare occasions, cauda equina syndrome and acute paraplegia have been the presenting signs. 3,9,10 The wide range of symptoms is partly due to adipose accumulation in different regions of the spinal canal. 1 Symptoms may develop acutely; although, most cases develop over months to years.…”
Section: Clinical Presentationmentioning
confidence: 99%